1998
DOI: 10.1051/agro:19980808
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in rate and extent of the in situ cell wall degradation of maize stalks at silage harvest time

Abstract: -Genetic variation in in situ degradability traits of the NDF part of maize stalks at silage harvest time has been studied, as part of the research for an ingestibility criterion in silage maize breeding, for 2 years with nine (including two brown-midrib-3 hybrids) and six hybrids, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2003
2003
2006
2006

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(12 reference statements)
0
1
0
1
Order By: Relevance
“…According to Minson and Wilson [142], Blaxter et al [44] first reported that voluntary intake was positively correlated with digestibility, and Hawkins et al [115] reported that voluntary intake was negatively correlated with lignin content. The rate of NDF degradation, measured in situ in fistulated animals, varied very significantly among genotypes [38,124]. Such a trait should be considered as being possibly related to a genotype's rumen-filling capacity, and as a consequence, to genotype ingestibility.…”
Section: Devising a Breeding Criterion For Genetic Improvement Of Ingmentioning
confidence: 99%
“…According to Minson and Wilson [142], Blaxter et al [44] first reported that voluntary intake was positively correlated with digestibility, and Hawkins et al [115] reported that voluntary intake was negatively correlated with lignin content. The rate of NDF degradation, measured in situ in fistulated animals, varied very significantly among genotypes [38,124]. Such a trait should be considered as being possibly related to a genotype's rumen-filling capacity, and as a consequence, to genotype ingestibility.…”
Section: Devising a Breeding Criterion For Genetic Improvement Of Ingmentioning
confidence: 99%
“…Silomaisreife (Haarhoff 1990) erreicht. Daraus ergibt sich die generelle Forderung, Sorten anzubauen, die einen höheren Anstieg in der Korn-TM bei gleichzeitig verzö-gerter Restpflanzenabreife ermöglichen (Hunter 1979 (Orth u. Kaufmann 1961;Giesecke u. Tiews 1966;Hunter 1979;Verasilp 1986;Hunt et al 1989;Südekum 1989;Argillier et al 1998;Barriere et al 1998;Casper et al 1999;Bal et al 2000;Tolera u (Waldo 1973;Sutton 1985;Orskov 1986;Cronje 2000;Hindle et al 2005). Der Nutzung der Bypass-Stärke sind dabei Grenzen gesetzt, die durch eine unzureichende Stärkeverdauung, begrenzte Glukoseabsorption, mikrobielle Fermentation der Glucose im Dünndarm, weitgehende Verstoffwechselung absorbierter Glucose im Darmepithel und einen begrenzten Glucosetransport zu den Zielorganen begründet werden (Matthe 2001).…”
Section: Abreife Erntestrategie Und Züchtungszielunclassified